Sultan II. Mahmud Döneminde Safranbolu’da Muhtarlık Teşkilatının Kurulması / Establishing of Mukhtar Organization in Safranbolu in the Period of Sultan Mahmud II - Sarıköse, Selma Turhan (Journal of History Culture and Art Research, 2017)
Abstract Sultan Mahmud II period is known as the period of reforms in Ottoman history. In spite of the important political problems in inside and outside that have taken place, important arrangements have been made in the structure of the state in this period. The central organization, army, education and provincial administration have been reorganized. As the tımar administration was abolished in the provincial administration in this period. The change of the provincial system towards the provincial system and the establishment of the mukhtar administration became effective. With the removal of the province organization, mukhtars were assigned instead of the imams who were unable to fulfill their obligatory mandate to increase the immigration to Istanbul. After the establishment of the mukhtar organization in the province first in Kastamonu province. Safranbolu is one of the first residential areas where the mukhtar organization was established. Safranbolu was located within the borders of Kastamonu province during this period. In this study, the establishment of the mukhtar organization in the center of Safranbolu and it’s surroundings the first elected mukhtars were evaluated within the archive documents. Öz Sultan II. Mahmud dönemi Osmanlı tarihinde reformlar dönemi olarak bilinmektedir. Yaşanan önemli iç ve dış siyasi sorunlara rağmen bu dönemde devletin teşkilat yapısında önemli düzenlemeler yapılmıştır. Merkez teşkilatı, ordu, eğitim ve taşra idaresi yeniden organize edilmiştir. Taşra idaresinde bu dönemde tımar teşkilatı kaldırıldığı gibi eyalet sisteminin vilayet sistemine doğru değişimi ve muhtarlık idaresinin kurulması taşrada yeniden düzenin sağlanmasında etkili olmuştur. Tımar teşkilatının kaldırılması ile İstanbul’a göçün artması idari düzenlemeyi zorunlu kılmış, görevini yerine getiremeyen imamlar yerine muhtarlar görevlendirilmiştir. İstanbul’dan sonra muhtarlık teşkilatı taşrada ilk önce Kastamonu vilayetinde kurulmuştur. Safranbolu bu dönemde Kastamonu vilayet sınırları içinde olup, muhtarlık teşkilatının kurulduğu ilk yerleşim yerlerinden biridir. Bu araştırmada Safranbolu’da muhtarlık teşkilatının kurulması ve seçilen ilk muhtarlar arşiv belgeleri çerçevesinde değerlendirilmiştir. <pre style="margin: 6pt 0cm; text-align: justify; line-height: 140%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">Sultan Mahmud II period is known as the period of reforms in Ottoman history. In spite of the important political problems inside and outside that have taken place, important arrangements have been made in the structure of the state in this period. The central organization, army, education and provincial administration have been reorganized. As the tımar administration was abolished in the provincial administration in this period. The change of the provincial system towards the provincial system and the establishment of the mukhtar administration became effective. With the removal of the province organization, mukhtars were assigned instead of the imams who were unable to fulfill their obligatory mandate to increase the immigration to Istanbul. After the establishment of the mukhtar organization in the province first in Kastamonu province. Safranbolu is one of the first residential areas where the mukhtar organization was established. Safranbolu was located within the borders of Kastamonu province during this period. In this study, the establishment of the mukhtar organization in the center of Safranbolu and it’s surroundings the first elected mukhtars were evaluated within the archive documents.